5u-3-2=-8

Add 2 to both sides of the equation.

5u-3=-8+2

Add -8 and 2.

5u-3=-6

5u-3=-6

Multiply each term by u-3 and simplify.

Multiply each term in 5u-3=-6 by u-3.

5u-3⋅(u-3)=-6⋅(u-3)

Cancel the common factor of u-3.

Cancel the common factor.

5u-3⋅(u-3)=-6⋅(u-3)

Rewrite the expression.

5=-6⋅(u-3)

5=-6⋅(u-3)

Simplify -6⋅(u-3).

Apply the distributive property.

5=-6u-6⋅-3

Multiply -6 by -3.

5=-6u+18

5=-6u+18

5=-6u+18

Rewrite the equation as -6u+18=5.

-6u+18=5

Move all terms not containing u to the right side of the equation.

Subtract 18 from both sides of the equation.

-6u=5-18

Subtract 18 from 5.

-6u=-13

-6u=-13

Divide each term by -6 and simplify.

Divide each term in -6u=-13 by -6.

-6u-6=-13-6

Cancel the common factor of -6.

Cancel the common factor.

-6u-6=-13-6

Divide u by 1.

u=-13-6

u=-13-6

Dividing two negative values results in a positive value.

u=136

u=136

u=136

The result can be shown in multiple forms.

Exact Form:

u=136

Decimal Form:

u=2.16‾

Mixed Number Form:

u=216

Solve for u 5/(u-3)-2=-8